Studies of the South African species of Eulophia R. Br. ex. Lindl. (Orchidaceae) - Hall, A V (Department of Biological Sciences, 2015)
The present work was undertaken to provide a much-needed taxonomic revision of the South African members of the genus Eulophia R.Br. ex Lindl. (Orchidaceae). To obtain data for delimiting and giving rank to taxa, studies were made of morphological variation, geographical distribution, cytology and ecology.